Impact of financial education on the entrepreneurial motivation of micros and small entrepreneurs in Camaragibe-PE (Research, Society and Development, 2022)
This article aims to relate the knowledge and habits about personal finance of micro and small entrepreneurs who work in the municipality of Camaragibe-PE with their motivation to continue to undertake. A quantitative research was carried out, applying a structured questionnaire adapted from the Halpern model to 329 local entrepreneurs. Data were analyzed using descriptive and multivariate statistics, relating the constructs “financial education”, “credit management”, “asset management” and “stress with financial events” to the motivation to continue to undertake. The construct “credit management” presented the highest coefficient of explanation in the motivation to undertake. The research concluded that financial education, despite not being an explanatory factor, has a positive impact on the intention to continue entrepreneurship.